(untitled) (Jurnal AbdiMas Nusa Mandiri, 2024)
This Community Service activity focuses on optimizing catches and financial management, including: socialization of seafood processing, digital marketing training, and financial management literacy assistance with the aim of improving the economic welfare of capture fishermen in Tanjung Sebauk, Tanjungpinang,. Through this approach, it is expected to increase the income of fishermen and encourage the economic independence of coastal communities. The method used is a socialization program and direct assistance to capture fishermen, focusing on the use of social media as a marketing platform and the application of simple financial management principles. Data were obtained through observation, interviews, and documentation of activities. The results of this activity show an increase in fishermen’s income after participating in the program, which is due to the expansion of market reach and better financial management. In conclusion, this mentoring program proved effective in empowering capture fishermen and encouraging them to become maritime entrepreneurs. However, support from all parties is needed to ensure the sustainability of the program and changes in fishermen’s behavior in the long run.